General medical claims for behavioral health patients in Japan - Kishi, Yasuhiro (The American journal of managed care, 2020)
ABSTRACT Objectives: To evaluate the magnitude of general medical claims expenditures (ie, medical service use) for individuals who use and do not use behavioral health (BH) services in the Japanese free-access medical insurance system to determine if BH patients use substantially more health services, as has consistently been reported in the United States. Am J Manag Care. 2020;26(6):256-261. https://doi.org/10.37765/ajmc.2020.43488 Takeaway Points This study evaluated the magnitude of general medical claims expenditures for patients with chronic medical illnesses who use and do not use behavioral health (BH) services in the Japanese medical insurance system. * Annual total and medical costs of BH service users were 1.6 times and 1.3 times higher, respectively, than those of non—BH service users. * Patients with concurrent BH conditions and chronic medical illnesses have substantially lower total health care costs than numerous studies have demonstrated in US populations. * This could be due, at least in part, to the integration of medical and BH claims payment in Japan. The interaction of behavioral health (BH) and general medical spending has been evaluated in several countries.1-5 Studies consistently show increased general medical service use and cost for those with BH disorders.3-5 Further, 86.8% of the cost for total health care in US patients with medical and BH comorbidities has been estimated to be for medical services.5 In patients covered by commercial insurance, the total costs of US patients with medical and BH comorbidities are 2.6 times higher than for those without BH comorbidities.5 In the United States, the reasons for higher medical cost among BH patients might be the nation's health care system, which includes disincentives to use BH care that were introduced by managed BH insurance practices6,7; difficulty in accessing BH services8; and/or loss of BH coverage. Study Population We included all health plan enrollees 18 years and older who visited a health care facility during the 3-month enrollment period (between April 2014 and June 2014); all had at least 1 diagnosis of a chronic medical condition and were enrolled in the database during the entire study period (between April 2014 and June 2015).